Extent shifts of Central Asian winter- and summer-rain domains since the last glacial period and their driving mechanisms - Haoru Wei; Yougui Song; Shugang Kang; Xiuling Chen; Yue Li; Mengxiu Zeng; Li Han; Tao Chen; Hamid Gholami; Saparov Galymzhan (CATENA, 2026)

Cyclodextrin-based supramolecular deep eutectic solvents modulate curcumin stabilization and the structure-property relationships of potato starch-PVA films - Bailiang Zheng; Shaohua Chen; Lin Chen; Xiuling Zhang; Zhili Pan (Food Research International, 2026)

From molecular interactions to functional enhancement: unraveling the non-covalent binding between Perilla seed protein fibrils and structurally diverse polyphenols - Xiquan Li; Shaohua Chen; Guangyu Xu; Xiuling Zhang; Zhili Pan; Weiwei Yang (Food Research International, 2026)

Identification of the SlRCC1 gene family and characterization of SlRCC1-13 in cold stress response in tomato (Solanum lycopersicum) - Huixin Zhang; Xueyao Zeng; Yixiao Bai; Yuxin Liu; Rui LV; Fulei Mo; Mingfang Feng; Shusen Liu; Xiuling Chen; Aoxue Wang (Plant Science, 2026)

Electronic metal-support interaction modulation via alumina phase engineering for enhanced Ru-catalyzed aromatic hydrogenation at room temperature - Ruiying Chai; Bixian Zhong; Fan Zhang; Xin Han; Shanguang Xu; Shanguo Du; Dairong Chen; Jie Zhang; Xiuling Jiao (Chemical Engineering Journal, 2026)

Steering Ce atoms as an electronic reservoir in Tpy-regulated Bi2Te3 nanosheets for enhanced CO2 reduction to formate - Yupeng Li; Xinrui Liu; Shu Liu; Dairong Chen; Xiuling Jiao; Yuguo Xia (Chemical Engineering Journal, 2026)

Integrating bionic water collecting fabric and 3D hydrogel for significantly enhanced solar-driven interfacial evaporation condensation performance - Qiao Li; Dairong Chen; Xiuling Jiao (Desalination, 2026)

Coordination chemistry-guided construction of hierarchical lignin-derived porous carbon with dual Lewis acid–base sites for synergistic CO2 capture - Xinxin Niu; Li Bai; Xiuling Xu; Fujun Wang; Shuai Zhu; Yixian Xue; Zhi Liu; Zhao Chen (Chemical Engineering Journal, 2026)

Microbial driving mechanisms of sludge reduction in modular wastewater treatment systems under surplus aeration regulation - Chen Chen; Haifeng Hao; Rujie Hao; Nan Yu; Xiuling Li (Journal of Environmental Management, 2026)

Trough concentration of voriconazole and its association with central nervous system toxicity in patients with hematologic malignancies: a retrospective cohort study - Qinghua Zhang; Junwei Chen; Wenming Tan; Weien Li; Lirong Tan; Xiuling Wen (European Journal of Clinical Pharmacology, 2026)

Rhizosphere microbial diversity and community assembly in tree species–slope aspect coupled mountain forests of the Qilian Mountains, northeastern Qinghai–Tibet Plateau - Hangyu Bai; Qian Chen; Xiuling Yang; Dengwu Li (Applied Soil Ecology, 2026)

Built-In electric field in BiVO4-SnO2 heterostructure for enhanced photoelectrochemical H2O2 production - Jiajia Cai; Zhi Zhang; Shixiang Zu; Aobo Cui; Xiuling Li; Qian Xie; Keke Mao; Jing Chen (Fuel, 2026)

Microbubble enhanced CO2-to-ethanol conversion for artificial CC condensation pathways - Wanrong Dong; Xiuling Ji; Boxia Guo; Haijun Yu; Dongbo Cai; Shouwen Chen; Yuhong Huang (Bioresource Technology, 2026)

Hydrogel-confined molecular iron catalyst enables enhanced selective photoelectrochemical oxidation of glycerol to glycolaldehyde - Lu Wang; Zizhong Chen; Qi Zhao; Xiuling Jiao; Dairong Chen; Yuguo Xia (Chemical Engineering Journal, 2026)

Characterization and source apportionment of heavy metal contamination in surface sediments from the Zhuyukou Waterway, Pingtan Island, Southeast China - Jianhua Liu; Xiuling Chen; Jie Liu; Binggui Cai; Yujie Guo (Regional Studies in Marine Science, 2025)

Blocking T-type calcium channels disrupts spermatogenesis in vivo and adversely affects spermatocytes in vitro by impairing mitochondrial function and autophagic flux - Xiuling Zhao; Lei Wang; Shiqin Huang; Lin Liu; Xiaorong Wang; Liping Pu; Hao Chen; Junyu Nie (Reproductive Toxicology, 2025)

Shift from ice sheet to winter insolation as a control on both wetting and dune stabilization in northern Xinjiang during the Holocene - Qiaowen Zhang; Licheng Guo; Shangfa Xiong; Zhizhong Li; Jingyi Cui; Xiuling Chen (Quaternary Science Reviews, 2025)

All-in-one electrochromic windows based on hydrogels containing dual redox pairs for affordable and large-scale applications - Yuling Zhu; Qi Zhao; Chenglong Mu; Yahui Liu; Yuguo Xia; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Ether-free PDMS-based composite electrolytes with intrinsic safety, high ionic conductivity and wide electrochemical window for solid state Li-metal batteries - Chenglong Mu; Jinyan Chen; Qi Zhao; Yahui Liu; Yuling Zhu; Zhang Dai; Xina Sui; Xiuling Jiao; Dairong Chen; Ting Wang (Chemical Engineering Journal, 2025)

Nocturnal near-surface ozone increases events in Beijing-Tianjin-Hebei region, China during 2018–2023 and the associated mechanisms - Xiuling Wang; Hui Zhang; Xiaochen Fei; Kai Meng; Junming Chen; Jiajia Hua; Fenglian Ma; Xiaodong Zhang; Guan Wang; Chengying Zhang (Meteorology and Atmospheric Physics, 2025)

New interpretation of the Rb/Sr ratio of the Ili loess, northeastern Central Asia - Yanping Wang; Yougui Song; Yue Li; Hamid Gholami; Haoru Wei; Mengxiu Zeng; Xiuling Chen; Li Han (Quaternary Science Reviews, 2025)

Geochemical evidence indicates that deserts are not the dominant source of loess in Central Asia - Yue Li; Yougui Song; Xiuling Chen; Dimitris G. Kaskaoutis; Hamid Gholami; Xiulan Zong; Shukhrat Shukurov; Nosir Shukurov (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Construction and characterization of Pickering emulsion stabilized by agar-phenylalanine complex microgel particles - Zizhou Chen; Xiuling Wang; MeixiLiu; Huifen Weng; Xiaoyan Zhuang; Anfeng Xiao; Qiong Xiao (Carbohydrate Polymers, 2025)

pH-regulated structural and interfacial properties of OSA starch/whey protein fiber complexes to improve the storage and digestive stability of citrus essential oil emulsions - Run Ji; Haowen Sun; Zhao Chen; Shuang Song; Hao Guo; Xiuling Zhang; Fei Wu (Carbohydrate Polymers, 2025)

An outcome-wide analysis of maternal air pollution exposure and adverse pregnancy outcomes in intrahepatic cholestasis of pregnancy - Xueqi Li; Xiuling Zhu; Daijuan Chen; Yajie Zhao; Xixi Deng; Yongchi Zhan; Bing Guo; Tingting Xu; Xiaodong Wang (Atmospheric Environment, 2025)

Woody Plant Encroachment Significantly Alters Grassland Soil Microbial Community: A Global Meta‐Analysis - Guoliang Sha; Shuyan Chen; Xuanchen Liu; Wanyu Xia; Hanwen Cui; Anning Zhang; Lizhe An; Zi Yang; Xia Zhao; Jing Zhang; Xiuling Yu; Jing Xiao; et al. (Global Ecology and Biogeography, 2025)
Aim Woody plant encroachment is reshaping grassland ecosystem functions worldwide. While its aboveground impacts are well documented, how this process alters microbial communities—key drivers of belowground processes—remains poorly understood. We aimed to (1) quantify the general effects of global woody plant encroachment on soil microbial community attributes in grasslands and (2) identify the abiotic and biotic factors driving these changes. Location Global grassland ecosystems. Time Period 2000–2024. Major Taxa Studied Soil microbial communities (bacteria, fungi). Methods We conducted a meta‐analysis of 241 paired observations to evaluate changes in microbial composition, diversity, biomass, activity and enzyme activity under woody plant encroachment. Results Woody plant encroachment significantly altered soil properties. Woody plant encroachment also promoted a comprehensive increase in microbial community diversity, biomass, microbial activity and enzyme activity, as well as changes in community composition. The nitrogen‐fixing status of the encroaching species (biotic factor) significantly affected microbial responses: encroachment by nitrogen‐fixing plants resulted in a higher abundance of Bacteroidetes, fungal richness, microbial biomass phosphorus and phosphatase activity compared to non‐nitrogen‐fixing plants. In addition, abiotic factors, such as mean annual temperature, soil organic carbon and total nitrogen were identified as key factors driving microbial responses. Specifically, mean annual precipitation, mean annual temperature and elevation jointly regulated the effects of woody plant encroachment on soil microbial community attributes by influencing plant and soil properties. Main Conclusions This meta‐analysis demonstrated that woody plant encroachment significantly reshaped soil microbial communities in grassland ecosystems. Our findings highlight the role of abiotic factors (climate, elevation, organic carbon and total nitrogen), and biotic factors (nitrogen‐fixing status) in mediating the response of soil microbial communities. These insights contribute to a better understanding of belowground ecological processes and provide valuable guidance for grassland management and predictions of biogeochemical cycles under global change.

Thermally triggered surface reconstruction enables self-protective layer for enhanced charge transfer in CdIn2S4 photoelectrode - Zizhong Chen; Lu Wang; Xiuling Jiao; Yuguo Xia; Dairong Chen (Chemical Engineering Journal, 2025)

Electronic structure modulating of PtFe dual-atom catalyst for efficient hydrogen splitting and almost 100 % selective hydrogenation of α,β-unsaturated aldehydes - Xinrui Liu; Yupeng Li; Dairong Chen; Xiuling Jiao; Yuguo Xia (Chemical Engineering Journal, 2025)

Synergistic role of Cu0 and acidic sites in Cu/Al2O3 catalysts for enhanced furfural hydrogenation to furfuryl alcohol - Shanguang Xu; Xin Han; Fan Zhang; Zhengyang Sun; Ruiying Chai; Fei Xu; Shanguo Du; Xiuling Jiao; Dairong Chen; Jie Zhang (Chemical Engineering Journal, 2025)

Identification of brevis radix (BRX) family genes in tomato (Solanum lycopersicum) and the function of SlBRX5 and SlBRX7 under cold stress - Xiuling Chen; Changhao Mao; Rui Lv; Hecheng Sun; Shusen Liu; Zhao Liu; Aoxue Wang (Plant Science, 2025)

Defect-mediated spatial confinement of Pt single atoms on photoactive CdIn2S4 octahedrons: Synergistic carrier dynamics optimization for photocatalytic hydrogen production - Zizhong Chen; Lu Wang; Xiuling Jiao; Yuguo Xia; Dairong Chen (Chemical Engineering Journal, 2025)

Rett syndrome: Pathogenicity and regulation of MECP2 (human) and Mecp2 (mouse) genes and their protein products through various molecular mechanisms - Bashir Ahmad; John Sieh Dumbuya; Ji-Xin Tang; Wen Li; Xiuling Chen; Jun Lu (Mutation Research - Reviews in Mutation Research, 2025)

Air heating-alkaline hydrothermal production of artificial humic acid: Rapid and efficient humification of waste biomass - Bo Yang; Jiliang Zheng; Yiwei Sun; Xinyu Chen; Xiuling Yan; Bekchanov Davronbek; Jinxiong Wu; Patrycja Boguta; Lijuan Zhang; Junli Ren; Xintai Su (Journal of Environmental Chemical Engineering, 2025)

Functional molecule surface infiltration treatment for efficient all-inorganic perovskite light-emitting diodes - Shurui Chi; Yongjian Chen; Xiuling Li; Jiaqi Wang; Zixun Zhao; Zhuojian Li; Yanqin Miao; Xin Tong; Jinli Liu; Yuechuan Bi; Zongwen Liu; Zhiming Wang; et al. (Chemical Engineering Journal, 2025)

Evaluation of the duration effect on the seismic fragility of subway stations considering different damage state thresholds - Qilong Han; Qiangqiang Sun; Zhongkai Huang; Hongjuan Chen; Xiuling Cao (Tunnelling and Underground Space Technology, 2025)

Effects of CSTB on in vitro maturation of ovine oocytes - Ying Chen; Gulimire Abudureyimu; Jiapeng Lin; Liqin Wang; Xiuling Ma; Xiangli Wu; Yangsheng Wu (Animal Reproduction Science, 2025)

Efficient preparation of potassium humate from waste vegetable leaves: Development of a Cu2O@HAK catalyst and innovative application of hydrothermal method - Jiamin Qi; Jiliang Zheng; Yatang Dai; Bo Yang; Haohao Bian; Xinyu Chen; Shunyu Yin; Xiuling Yan; Xiaoyan He; Hongguang Zhao; Yanjie Ren; Changchun Ge; et al. (Journal of Environmental Chemical Engineering, 2025)

Application of composite biological control agent in postharvest preservation of cherry tomatoes - Fanyue Meng; Mozhen Cheng; Ziqi Zhou; Peiwen Wang; Shusen Liu; Zhao Liu; Zhengfeng Song; Xiuling Chen; Aoxue Wang (Physiological and Molecular Plant Pathology, 2025)

Ultra-stable zinc-ion hybrid capacitors empowered by hydrogel electrolyte programmed with chain-additive approach - Xiuling Dong; Xinyi Ge; Wei Chen; Shuangqing Li; Zheng Xing; Zhong-Xia Wang; Qingguo Zhang (Chemical Engineering Journal, 2025)

Comprehensive metabolome and transcriptome analyses shed light on the regulation of SlNF-YA3b in carotenoid biosynthesis in tomato fruit - Peiwen Wang; Siyu Ran; Yuanhang Xu; Fulei Mo; Fengshuo Li; Rui Lv; Fanyue Meng; Huixin Zhang; Yuxin Zou; Lei Yu; Tianyue Yu; Mozhen Cheng; et al. (Postharvest Biology and Technology, 2025)

Double-layer Janus sponge evaporator: Optimal balancing between evaporation efficiency and salt resistance - Qiao Li; Dairong Chen; Xiuling Jiao (Chemical Engineering Journal, 2025)

Triggering efficient redox cycling and electron transporting in CuCo spinel oxides via oxygen vacancy building for rapid degradation of antibiotics - Longlong Geng; Fengting Geng; Xianghan Cheng; Man Yang; Xiaoli Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Wenyuan Han; Shujuan Zhuang; Yuting Chen; Guangzhi Hu (Chemical Engineering Journal, 2024)

Study of the electrospun PVDF fibrous membrane in capturing particulate matters in smoke by the synergy between GO and CNWs - Xiuling Lin; Jieqi Zhang; Ge Meng; Chao Zhang; Chen Yu (Chemical Engineering Journal, 2024)

Ca2+/ethanol driven in-situ integration of tough, antifreezing and conductive silk fibroin/polyacrylamide hydrogels for wearable sensors and electronic skin - Guangdong Sun; Xiuling He; Haixia Chen; Jinchao Li; Yongqiang Wang (Chemical Engineering Journal, 2024)

NaCl improves the vegetable quality of Mesembryanthemum crystallinum Linn. by increasing betacyanin and nutrient contents - Yanlu Liu; Qing Liu; Xiuling Liu; Yang Zhao; Yun Liu; Baoshan Wang; Min Chen (Plant and Soil, 2024)

Effect of metal cation crosslinking on the mechanical properties and shrimp freshness monitoring sensitivity of pectin/carboxymethyl cellulose sodium/anthocyanin intelligent films - Run Ji; Xinhua Zhang; Zhao Chen; Shuang Song; Yingying Li; Xiuling Zhang; Wentao Zhang (Carbohydrate Polymers, 2024)

Re-evaluating the origins of sands in the Gurbantunggut Desert and its role as an aeolian dust contributor - Yue Li; Yougui Song; Yu’an Guo; Peng Liang; Xiuling Chen; Jingyun Xiao; Shukhrat Shukurov; Yudong Li (Global and Planetary Change, 2024)

A temperature-responsive, repairable and renewable self-floating hydrogel steam generator - Qiao Li; Longfei Guo; Dairong Chen; Xiuling Jiao (Chemical Engineering Journal, 2024)

Sedimentary characteristics of ion-adsorption rare earth elements and assessment of their resource reuse potential due to soil and water erosion in western Fujian - Chen Xiaowei; Chen Xiuling; Chen Zhibiao; Cai Binggui; Chen Zhiqiang; Li Yue; Chen Feiyan; Wang Yi; Fan Yifei; Liu Jie (Environmental Monitoring and Assessment, 2024)

Inhibitory effect and action mechanism of perillaldehyde on the Fusarium graminearum in postharvest fresh ginger - Xiuling Meng; Weijie Wu; Ben Niu; Ruiling Liu; Huizhi Chen; Haiyan Gao; Hangjun Chen (Postharvest Biology and Technology, 2024)

Electric field mitigates NH3 and N2O emissions during bioconversion of dairy manure by black soldier fly - Junfang Zhang; Long Chen; Shanshan Zhao; Dejia Hou; Wenjie Qin; Xiuling Zhu; Lei Luo; Deju Chen; Jeffery K. Tomberlin; Zhenyu Zhang; Qing Li (Chemical Engineering Journal, 2024)

Magnetic dendritic mesoporous silica nanoparticles based integrated platform for rapid and efficient analysis of saccharides - Xiuling Zhao; Jiacheng Dong; Yaqian Zhang; Tianrun Wu; Zijun Bie; Yang Chen (Analytica Chimica Acta, 2024)

Combined use of Trichoderma harzianum and Clonostachys rosea to manage Botrytis cinerea infection in tomato plants - Fengshuo Li; Hossien Ghanizadeh; Wenwei Song; Shuang Miao; Hui Wang; Xiuling Chen; Jiayin Liu; Aoxue Wang (European Journal of Plant Pathology, 2023)

Efficacy of a porcine reproductive and respiratory syndrome virus 1 (PRRSV-1) natural recombinant against a heterologous PRRSV-1 isolate both clustered within the subgroup of BJEU06-1-like isolates - Chen Li; Shuai Li; Shubin Li; Ming Qiu; Hong Lin; Zhe Sun; Yuejia Qiu; Wenhao Qi; Binghui Feng; Jixiang Li; Wanglong Zheng; Xiuling Yu; et al. (Veterinary Microbiology, 2023)

Unraveling source-to-sink dust transport in Central and East Asia by identifying provenances of aeolian sediments - Yue Li; Peng Liang; Yougui Song; Xinzhou Li; Shengli Yang; Xiuling Chen; Xiulan Zong; Nosir Shukurov; Yudong Li (Atmospheric Research, 2023)

Nitrogen addition influences fine root growth and mycorrhizal symbiosis formation in trees with contrasting root morphology - Xiaomin Ma; Xiuling Ni; Zhiming Guo; Xiaojun Zou; Jie Chen; Weijun Shen; Yakov Kuzyakov (Applied Soil Ecology, 2023)

Facile one-pot synthesis of multifunctional tetracycline hydrochloride nanoparticles with high stability and photothermal effect for synergistically improved antibacterial performance and sustainability - Mingzhou Lu; Weitao Wang; Xiuling Fang; Yang Xuan; Liying Chen; Xiaojing Wang; Jianhao Wang; Cheng Wang (Sustainable Chemistry and Pharmacy, 2023)

Late Pleistocene dynamics of dust emissions related to westerlies revealed by quantifying loess provenance changes in North Tian Shan, Central Asia - Yue Li; Yougui Song; Xiuling Chen; Zhengguo Shi; Dimitris G. Kaskaoutis; Hamid Gholami; Yudong Li (CATENA, 2023)

Time-frequency connectedness and cross-quantile dependence between carbon emission trading and commodity markets: Evidence from China - Haozhi Qi; Tiantian Wu; Hao Chen; Xiuling Lu (Resources Policy, 2023)

Correction to: Evaluation of salinity resistance and combining ability analysis in the seedlings of mulberry hybrids (Morus alba L.) - Xiuling Chen; Yujun Gao; Donghao Zhang; Yanxia Gao; Yongxue Song; Hui Wang; Baojun Ma; Jisheng Li (Physiology and Molecular Biology of Plants, 2023)

Microbiome - based agents can optimize composting of agricultural wastes by modifying microbial communities - Fengshuo Li; Hossein Ghanizadeh; Guangliang Cui; Jiayin Liu; Shuang Miao; Chang Liu; Wenwei Song; Xiuling Chen; Mozhen Cheng; Peiwen Wang; Yao Zhang; Aoxue Wang (Bioresource Technology, 2023)

Evaluation of salinity resistance and combining ability analysis in the seedlings of mulberry hybrids (Morus alba L.) - Xiuling Chen; Yujun Gao; Donghao Zhang; Yanxia Gao; Yongxue Song; Hui Wang; Baojun Ma; Jisheng Li (Physiology and Molecular Biology of Plants, 2023)

Development and characterization of yeast-incorporated coating films for improving the postharvest shelf-life of snap beans - Xinmao Li; Hossein Ghanizadeh; Zhengyuan Han; Tiantian Li; Yinghui Li; Zhitao Dou; Youwen Qiu; Xiuling Chen; Yao Zhang; Jiayin Liu; Aoxue Wang (Postharvest Biology and Technology, 2023)

Estrogen upregulates DNA2 expression through the PI3K-AKT pathway in endometrial carcinoma - Xinyan Wang; Xiuling Xu; Ting Zhang; Yang Jin; Sheng Xu; Lifeng Chen; Yucheng Lai; Ling Zhang; Ruolang Pan; Yan Yu (Journal of Zhejiang University-SCIENCE B, 2023)

Ag-organic coordination polymers with multi-dimensional electron transfer channels for enhancing CO2 electroreduction - Yingbing Zou; Tangxing Pan; Zhiwen Fan; Yunbin Li; Hao Zhang; Yan Ju; Yongfan Zhang; Xiuling Ma; Qianhuo Chen; Shengchang Xiang; Zhangjing Zhang (Chemical Engineering Journal, 2023)

The star target in SLE: IL-17 - Yi Yang; Chen Yan; Le Yu; Xiuling Zhang; Jingjing Shang; Jie Fan; Rongwei Zhang; Jie Ren; Xinwang Duan (Inflammation Research, 2023)

Genome-wide identification and expression analysis of the SlNAC gene family in tomato based on a high-quality genome - Xiuling Chen; Fulei Mo; Chunyang Shen; Lingjun Meng; Yuxin Zou; Xiaopeng Xue; Mozhen Cheng; Fanyue Meng; Haonan Qi; Aoxue Wang (Horticulture, Environment, and Biotechnology, 2022)

Improved spring temperature reconstruction using earlywood blue intensity in southeastern China - Xinguang Cao; Hongbing Hu; Pei‐ken Kao; Brendan M. Buckley; Zhipeng Dong; Xiuling Chen; Feifei Zhou; Keyan Fang (International Journal of Climatology, 2022)
Because instrumental observations are too short to fully represent long‐term natural variability, high‐resolution temperature proxy records are essential to understanding past climate and assessing current climate variability in the context of long‐term patterns. In the subtropics, progress in this field has been hampered by a relative lack of long and truly temperature‐sensitive proxy records. In this study, we provide an assessment of the dendroclimatic potential of blue intensity (BI) and ring‐width (RW) measurements from two hot/humid Pinus massoniana sites in China. Our results show that RW exhibits a significant ( p

The impact of TOPBP1 mutations in human cancers on the DNA damage response - Zhenzhen Yan; Xiuling Ge; Jiaxu Wang; Feng Xu; Mengyao Li; Xiuhua Liu; Xiaochun Yu; Chen Wu (Genome Instability & Disease, 2022)

The Sm gene conferring resistance to gray leaf spot disease encodes an NBS-LRR (nucleotide-binding site-leucine-rich repeat) plant resistance protein in tomato - Huanhuan Yang; Hexuan Wang; Jingbin Jiang; Mingyue Liu; Zengbing Liu; Yinxiao Tan; Tingting Zhao; He Zhang; Xiuling Chen; Jingfu Li; Aoxue Wang; Minmin Du; et al. (Theoretical and Applied Genetics, 2022)

Effects of polystyrene microplastics on copper toxicity to the protozoan Euglena gracilis: emphasis on different evaluation methods, photosynthesis, and metal accumulation - Xiuling Li; Zhengjun Wang; Ming Bai; Zhehua Chen; Gan Gu; Xi Li; Changwei Hu; Xuezhen Zhang (Environmental Science and Pollution Research, 2022)

Three Dimensional Statistical Damage Constitutive Model of Rock Based on Griffith Strength Criterion - Song Chen; Xiuling Cao; Zhao Yang (Geotechnical and Geological Engineering, 2021)

Calculation method and statistical characteristics of loosening pressure of a shallow-buried long-span tunnel in composite rock layer with random joint network - Song Chen; Xiuling Cao; Chunsheng Qiao; Zhao Yang; Chaozheng Qiao (Arabian Journal of Geosciences, 2021)

DCLK1 inhibition attenuates tumorigenesis and improves chemosensitivity in esophageal squamous cell carcinoma by inhibiting β-catenin/c-Myc signaling - Lianqun Zhang; Shengli Zhou; Ertao Guo; Xiaoqi Chen; Jun Yang; Xiuling Li (Pflügers Archiv - European Journal of Physiology, 2020)

Exposure to copper altered the intestinal microbiota in Chinese brown frog (Rana chensinensis) - Yijie Yang; Xiuling Song; Aixia Chen; Hongyuan Wang; Lihong Chai (Environmental Science and Pollution Research, 2020)

Sepsis-related myocardial injury is associated with Mst1 upregulation, mitochondrial dysfunction and the Drp1/F-actin signaling pathway - Xiuling Shang; Jun Li; Rongguo Yu; Pengli Zhu; Yingrui Zhang; Jingqing Xu; Kaihua Chen; Min Li (Journal of Molecular Histology, 2019)

Adaptive growth response of exotic Elaeagnus angustifolia L. to indigenous saline soil and its beneficial effects on the soil system in the Yellow River Delta, China - Yan Qi; Junpeng Li; Chunxiao Chen; Lingxiao Li; Xiuling Zheng; Jing Liu; Tingting Zhu; Caihong Pang; Baoshan Wang; Min Chen (Trees, 2018)

Physiological and RNA-seq analyses provide insights into the response mechanism of the Cf-10-mediated resistance to Cladosporium fulvum infection in tomato - Guan Liu; Junfang Liu; Chunli Zhang; Xiaoqing You; Tingting Zhao; Jingbin Jiang; Xiuling Chen; He Zhang; Huanhuan Yang; Dongye Zhang; Chong Du; Jingfu Li; et al. (Plant Molecular Biology, 2018)

Native promoters of Corynebacterium glutamicum and its application in l-lysine production - Xiuling Shang; Xin Chai; Xuemei Lu; Yuan Li; Yun Zhang; Guoqiang Wang; Chen Zhang; Shuwen Liu; Yu Zhang; Jiyin Ma; Tingyi Wen (Biotechnology Letters, 2018)

Upregulation of hydroxysteroid sulfotransferase 2B1b promotes hepatic oval cell proliferation by modulating oxysterol-induced LXR activation in a mouse model of liver injury - Zhengyang Wang; Xiaoming Yang; Liang Chen; Xiuling Zhi; Hanyu Lu; Yanxia Ning; Joe Yeong; Sifeng Chen; Lianhua Yin; Xinhong Wang; Xiaobo Li (Archives of Toxicology, 2017)

Spatial and temporal variability of thermal stress to China’s coral reefs in South China Sea - Xiuling Zuo; Fenzhen Su; Wenzhou Wu; Zhike Chen; Wei Shi (Chinese Geographical Science, 2015)

Plastid DNA insertions in plant nuclear genomes: the sites, abundance and ages, and a predicted promoter analysis - Hongyu Chen; Ying Yu; Xiuling Chen; Zhenzhu Zhang; Chao Gong; Jingfu Li; Aoxue Wang (Functional & Integrative Genomics, 2015)

Activation of elements in HERV-W family by caffeine and aspirin - Chunlan Liu; Yatang Chen; Shan Li; Honglian Yu; Jie Zeng; Xiuling Wang; Fan Zhu (Virus Genes, 2013)

Two natural recombinant highly pathogenic porcine reproductive and respiratory syndrome viruses with different pathogenicities - Nanhua Chen; Xiuling Yu; Lilin Wang; Jiajun Wu; Zhi Zhou; Jianqiang Ni; Xiangdong Li; Xinyan Zhai; Kegong Tian (Virus Genes, 2013)

Compressibility and structural properties of jadeite, NaAlSi2O6 at high pressure - Xiuling Wu; Xiaoyu Fan; Fei Qin; Dawei Meng; Xiaoling Zhang; Long Chen; Weiping Liu; Jianping Zheng (Journal of Earth Science, 2013)

Improving cooking and eating quality of Xieyou57, an elite indica hybrid rice, by marker-assisted selection of the Wx locus - Dahu Ni; Shilu Zhang; Sheng Chen; Yong Xu; Li Li; Hao Li; Zongyang Wang; Xiuling Cai; Zefu Li; Jianbo Yang (Euphytica, 2011)

Bio-geomorphologic features and growth process of Tamarix nabkhas in Hotan River Basin, Xinjiang - Zhizhong Li; Shengli Wu; Shujiang Chen; Xiuling Chen; Jianhui Jin; Qi Liu (Journal of Geographical Sciences, 2010)

Self-Assembled Hydrophobic Honokiol Loaded MPEG-PCL Diblock Copolymer Micelles - MaLing Gou; XiuLing Zheng; Ke Men; Juan Zhang; BiLan Wang; Lei Lv; XiuHong Wang; YinLan Zhao; Feng Luo; LiJuan Chen; Xia Zhao; YuQuan Wei; et al. (Pharmaceutical Research, 2009)

Developing drainage as the basis of comprehensive control of drought, waterlogging, salinity and saline groundwater - Fang Sheng; Chen Xiuling (Irrigation and Drainage, 2007)

RNA interference of ecto-5′-nucleotidase (CD73) inhibits human breast cancer cell growth and invasion - Xiuling Zhi; Sifeng Chen; Ping Zhou; Zhimin Shao; Li Wang; Zhouluo Ou; Lianhua Yin (Clinical & Experimental Metastasis, 2007)

Fracture detection by using full azimuth P wave attributes - Qu Shouli; Ji Yuxin; Wang Xin; Wang Xiuling; Chen Xinrong; Shen Guoqiang (Applied Geophysics, 2007)

A scheme for pixel-scale aerodynamic surface temperature over hilly land - Wenbin Min; Zhongming Chen; Linsheng Sun; Wenliang Gao; Xiuling Luo; Tingrong Yang; Jian Pu; Guanglun Huang; Xiurong Yang (Advances in Atmospheric Sciences, 2004)

Stable Inheritance of the Antisense Waxy Gene in Transgenic Rice with Reduced Amylose Level and Improved Quality - Qiaoquan Liu; Zongyang Wang; Xiuhua Chen; Xiuling Cai; Shuzhu Tang; Hengxiu Yu; Jinliu Zhang; Menming Hong; Minghong Gu (Transgenic Research, 2003)